A novel fixed switching frequency control strategy applied to an improved five-level active rectifier - Monteiro, Vítor Duarte Fernandes (2018)
A novel fixed switching frequency control strategy applied to an improved five-level active rectifier (iFLAR) is proposed. The operation with fixed switching frequency represents a powerful advantage, since the range of the produced harmonics is well identified, and it is possible to design passive filters to mitigate such harmonics. The experimental validation shows that the control strategy allows attaining an ac-side current with reduced total harmonic distortion and high power factor, which is an attractive influence for grid-connected electrical appliances. This contribution is even more relevant with the new paradigm of smart grids where higher levels of power quality are required. A theoretical analysis of the control strategy and the details of its implementation in a digital signal processor are presented. The control scheme and the developed iFLAR were experimentally confirmed using a laboratorial prototype, showing its benefits in terms of accuracy, reduced total harmonic distortion and high power factor.